Cost analysis of library functions : a total system approach - Mitchell, Betty Jo.; Tanis, Norman E.; Jaffe, Jack. (Greenwich, Conn. : Jai Press, 1978)
This monograph attempts to deal with the cost side of the trade-off equation, and specifically limited to the subject if labor cost in time and dollars .
Includes bibliographical references and index.
oo 22/01/2019
Loans
Keywords: Library finance; Cost accounting; Library administration